IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN AL-QURAN HADIST DI MADRASAH TSANAWIYAH ISLAMIYAH DEPOK - nurasna, azizah; Aminie, Aisya; Faridah, Eva Siti (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The 2013 curriculum is very different from other curricula. There are still many obstacles that we know greatly affect learning outcomes, both from the media used, assessment in the 2013 curriculum is more complicated than other curricula. Such as the study of the Quran and Al-hadith. There are still many shortcomings that are obtained due to the lack of learning media and the strategies used by teachers are still monotonous. The school curriculum of Madrasah Tsanawiyah at MTS Islamiyyah still uses the 2013 Curriculum as a guideline for classroom learning. The type of research used is qualitative research with a case study method. By doing class actions twice to find out the state of the class and the learning process. To find out how the implementation of the 2013 curriculum in MTS Islamiyah Sawangan schools, and the classroom learning process carried out by teachers. Data collection through interviews, as well as observation to schools and seeing the learning process. Understand the lesson plans and syllabus that have been made by teachers. Keyword : curriculum 2013, Madrasah Tsanawiyah, Al-Quran and Hadith